PERTANYAAN TRADISIONAL MASYARAKAT DI KENAGARIAN SUNGAI PINANG KECAMATAN KOTO XI TARUSAN KABUPATEN PESISIR SELATAN - Oktafrian, Antoni; Hasanuddin WS, Hasanuddin WS; Nurizzati, Nurizzati (Jurnal Bahasa dan Sastra, 2018)
This study aims to describe: (1) the traditional question structure of the community in Kenagarian Sungai Pinang, Koto XI Subdistrict, Tarusan, South Pesisir Regency: (2) the category of traditional questions of the community in Kenagarian Sungai Pinang, Koto XI Subdistrict, Tarusan, South Pesisir Regency: (3) Community Social Functions in Kenagarian Sungai Pinang Koto XI Subdistrict Tarusan South Pesisir Regency. This type of research is qualitative research using descriptive methods. This research data is a traditional question of the community in Kenagarian Sungai Pinang, Koto XI Sub-District, Tarusan, South Pesisir Regency. Data were collected from informants through interview techniques, observation and recording of interviews with informants. Based on the results of the study found the following: (1) the structure of traditional community questions in Kenagarian Sungai Pinang, Koto XI Subdistrict Tarusan, Pesisir Selatan Regency consists of: (a) traditional questions that are contradictory, and (b) traditional questions that do not contradict: (2 ) category of traditional community questions in Kenagarian Sungai Pinang Koto XI Subdistrict Tarusan Pesisir Selatan Regency consists of: (a) similarities with living things, (b) similarities with animals, (c) similarities with some animals, (d) similarities with humans, (e) similarities with some people, (f) similarities with plants, (g) equality with objects, (h) equation with parables, (i) equation with form and function, (j) equation with matter, and (k) equation with actions: (3) the social function of the traditional question of the Community in Kenagarian Sungai Pinang, Koto XI Sub-district Tarusan, South Pesisir Regency consists of: (a) testing the intelligence of others, and (b) amuse.Keywords: Structure, Category, Social Function